Dramaturgi Anak Pengamen Boneka: Pengelolaan Identitas Ganda sebagai Pelajar dan Pekerja Informal di Kota Palopo - Muhammad Ashabul Kahfi; Bahtiar Bahtiar; Fitriani Jamaluddin; Andini Andini (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze how school-aged mascot buskers in Palopo City construct, perform, and negotiate their social identities as both students and street entertainers. The research employed a qualitative approach grounded in Erving Goffman’s dramaturgical perspective. Data were collected through observation, in-depth interviews with seven mascot busker children, and documentation involving school-enrolled child mascot buskers in Palopo City. The findings reveal that the social lives of these children are organized through a clear separation between front-stage and back-stage spaces. Public spaces function as the front stage, where an entertaining persona is produced through costume, bodily performance, and impression management, while school and family settings serve as the backstage, where their student identity is preserved. The mascot costume was found to serve a dual function: as a means of economic production and as a mechanism for protecting social identity. The findings further indicate that identity negotiation is consciously managed through the separation of time, space, and audiences in order to avoid stigma from the school environment. Theoretically, this study extends Goffman’s dramaturgical perspective to the context of informal child workers who remain actively engaged in formal education, demonstrating that visual symbols function not only to construct impressions but also to safeguard the continuity of social identity. Practically, the findings underscore the importance of school support systems and public space policies that are more responsive to children from informal working families.